A 3D finite element stochastic framework for the failure of tow-based discontinuous composites. (8th February 2023) - Alves, M.; Martulli, L.M.; Kerschbaum, M.; Swolfs, Y.; Lomov, S.V.; Pimenta, S.
Abstract: Tow-Based Discontinuous Composites (TBDCs) combine high manufacturability with good mechanical properties. This work presents a novel 3D approach for the numerical modelling of TBDCs. The framework generates 3D orientation tensors by adding a stochastic component to the orientation tensors deterministically predicted by a process simulation. The actual TBDCs are thus idealised as Equivalent Laminates (ELs), resulting from these stochastic tensors. A physically based 3D failure criterion is presented for the prediction of failure initiation of the ELs. The consequent stiffness reduction is captured by a ply-discount method. The approach is validated for two TBDCs materials, with two different moulding conditions and different amounts of in-mould flow. The proposed approach accurately predicts the characteristic variability of these materials. As a consequence, the predicted strength was in good agreement with the experimental results of both materials tested. Graphical abstract: